Translation of Twenty Yemeni Short Stories: Evaluation of the Problems and the Strategies Employed - Al-Haj, Na'amah; Jibreel, Ibrahim; Sharafuddin, Mohammed; Al-Shameri, Huthaifa H (International Journal of English Language & Translation Studies, 2021)
Cultural items are part and parcel of any culture and their translation is one of the most difficult tasks a translator may encounter. This research paper attempts to evaluate the translation of short stories shedding light on some problematic areas of literary translation (i.e., metaphors, idioms, irony, etc.) that play a significant role in characterizing a literary text. It also aims to identify the strategies applied by the translator in rendering such problematic areas into the TL with evaluative commentaries. The comparative descriptive method was followed. The 20 story translations were randomly selected out of 40 Yemeni short stories done by Dr. Shirin Mohammed. Researchers evaluated the translation using the triangulation method. First, the problems were identified through a qualitative analytical comparison of the ST to the TT. Then, frequencies and percentages were quantitatively used to determine the size of each translation strategy adopted by the translator (literal translation, free translation, translation by Paraphrasing, translation by Omission, Transliteration) in relation to the translation of literary problem type (metaphors, idioms, proverbs, irony, religious expressions, cultural-specific lexical items, illusion). Results show that the most three problematic areas are idioms, religious expressions, and cultural-specific lexical items respectively. On the other hand, the less problematic areas are metaphors and allusions with the same rank, irony, and proverbs respectively. In addition, the most frequently used strategy is literal translation, followed by paraphrasing, omission, free translation, and transliteration. The strategic-problem tactic of the translator shows ST is mostly rendered word-for-word into the TT which demonstrates how the translator is stuck to the ST lexis. Ineffective and inadequate uses of the strategy of omission result in an unnecessary exclusion of some idioms and religious expressions. Although transliteration endows the TT with local colour and atmosphere, it hampers the TT reader’s comprehension when it is used without adding explanatory notes. Occasionally, the translator fails to achieve comprehension at the ST level and understand the ST intended message. Therefore, the outcome is a mistranslation. However, the use of translation by paraphrasing and free translation establish bridges of effectiveness and acceptability between the ST and TT.
Keywords: Literary Translation; Evaluation; Translation Quality; Yemeni; Short Stories